Lives saved and hospitalizations averted by COVID-19 vaccination in New York City: a modeling study - Affan Shoukat; Thomas N. Vilches; Seyed M. Moghadas; Pratha Sah; Eric C. Schneider; Jaimie Shaff; Alexandra Ternier; Dave A. Chokshi; Alison P. Galvani (Elsevier, 2022)
Summary: Background: Following the start of COVID-19 vaccination in New York City (NYC), cases have declined over 10-fold from the outbreak peak in January 2020, despite the emergence of highly transmissible variants. We evaluated the impact of NYC's vaccination campaign on saving lives as well as averting hospitalizations and cases. Methods: We used an age-stratified agent-based model of COVID-19 to include transmission dynamics of Alpha, Gamma, Delta and Iota variants as identified in NYC. The model was calibrated and fitted to reported incidence in NYC, accounting for the relative transmissibility of each variant and vaccination rollout data. We simulated COVID-19 outbreak in NYC under the counterfactual scenario of no vaccination and compared the resulting disease burden with the number of cases, hospitalizations and deaths reported under the actual pace of vaccination. Findings: We found that without vaccination, there would have been a spring-wave of COVID-19 in NYC due to the spread of Alpha and Delta variants. The COVID-19 vaccination campaign in NYC prevented such a wave, and averted 290,467 (95% CrI: 232,551 - 342,664) cases, 48,076 (95% CrI: 42,264 - 53,301) hospitalizations, and 8,508 (95% CrI: 7,374 - 9,543) deaths from December 14, 2020 to July 15, 2021. Interpretation: Our study demonstrates that the vaccination program in NYC was instrumental to substantially reducing the COVID-19 burden and suppressing a surge of cases attributable to more transmissible variants. As the Delta variant sweeps predominantly among unvaccinated individuals, our findings underscore the urgent need to accelerate vaccine uptake and close the vaccination coverage gaps. Funding: This study was supported by The Commonwealth Fund.